“PEKA PENGAJAR” PENGABDIAN KOMUNIKASI PENDIDIKAN DI SAUNG BACA GARPU DAN RUMAH BELAJAR KAPUK - Azeharie, Suzy; Margareth, Hanna; Hutama, Victor; Aulia, Shabila; Wicaksono, Raihan Zahran; Marlene Sandra; Noho, Nabir I.B. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Education is a very important investment for the progress of a country. Indonesia is one of the countries that implements one of the points of Indonesian citizens' rights contained in Article 31 Paragraph 1, namely all citizen have the righs to a quality education tailored to their individual interest and talent. Education first comes from the family environment, then the school environment, and the community environment. However, in Indonesia, not all children are able to receive an appropriate education due to a lack of awareness of the important of education, economic disadvantage, and educational disparities which results in many children being reluctant to go to school and some of them even choose to drop out of school. Saung Baca Garpu and Rumah Belajar Kapuk are one of example. These two places are alternative schools that were founded to help children who have economic disadvantages and to embrace children who previously had no interest in learning to want to learn, at least they can recognize letters and numbers so that later they can write and read counting. From here their mindset was formed, that learning is just writing and reading. With this, the PEKA PENGAJAR Team was moved to make teaching and learning activities more enjoyable. By using team teaching methods, creativity methods, competition methods, and socialization methods. Therefore, from the activities that we have carried out, we have obtained results that children prefer to learn to be accompanied by quizzes and also change the mindset of children that learning is not only about writing but understanding what is conveyed. We really hope that the method we apply can increase children's interest in learning, and can be useful and beneficial for children's lives.